A global analysis of plant nutrient limitation affected by atmospheric nitrogen and phosphorous deposition - Du, Lan; Tang, Lisong; Zheng, Xinjun; Li, Yan (Frontiers in Plant Science, 2024)
Uncovering the response of plant functional types (PFTs) to nutrient limitation caused by atmospheric deposition is critical for assessing the health of terrestrial ecosystems under climate change conditions. However, it remains unclear how atmospheric deposition and underlying ecological factors affect PFTs globally. To address this, we compiled a global dataset of four PFTs, i.e., herb, evergreen broad-leaf (EB), deciduous broad-leaf (DB), and conifer (CO), and utilized both linear mixed-effects models and structural equation models to describe the thresholds of their net primary productivity (NPP), and tested the relationships between their NPP and potential environmental drivers based on the N/P threshold hypothesis. We found that atmospheric N and P deposition non-linearly affected NPP and the effects were most pronounced for the EB, DB, and CO categories, with tipping points in the ranges of 8.32–9.33 kg N·ha−1·yr−1 and 0.20–0.30 kg P·ha−1·yr−1, respectively. Atmospheric N and P deposition negatively affected the NPP of approximately 53.68% and 43.88% of terrestrial ecosystem plants, respectively, suggesting increased P limitation and N saturation in most terrestrial ecosystems worldwide. We further determined that the N/P threshold hypothesis is applicable in assessing the effects of atmospheric N and P deposition on the growth of woody plants (EB, DB, and CO) through nutrient limitation. The results of this study will contribute to more effective landscape management in changing environments.